Effect of adding Ag on tensile and microstructure properties of zinc alloy - Mohd Azizan, Farihan; Purwanto, Hadi; Mustafa, Mohd. Yusry (IJENS Publishers, 2012)
Silver additions between 0.03 wt.% to 0.50 wt.% were made to the Zn- 20Sn (wt.%) in an attempt to develop Zinc based alloy for application and improvement in giftware industry. In this study, we investigated the effect of Ag addition on Zn based alloy and mechanical properties of Zn-Sn-Ag alloys with variation of Ag contents. The measured mechanical properties are tensile strength and percentage elongation. It was found that addition of Ag over the entire range of concentrations has a useful effect on tensile properties of the alloy. Furthermore, the percentage elongation and tensile strength of the samples also increases with further increase in Ag content. Alloy containing 0.50 wt.% showed the highest value in both tensile strength and percentage elongation. Thus, the mechanical properties of the alloy improved with increasing Ag percentage up to 0.50 wt. %. On the other hand, increasing Ag content also significantly affected the fracture surface of the alloys. The surface showed a mixed mode of fracture exhibiting ductile failure and brittle failure. Metallographic studies showed that the addition of Ag resulted in microstructure modifications of the alloy involving the formation of intermetallic compound identified as Ag3Sn and AgZn which decrease the precipitation of Zn in Sn matrix. The microstructure results also affected the mechanical properties of alloy by the presence of the elements.